2022
DOI: 10.1002/cne.25293
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of experimental glaucoma on intrinsically photosensitive retinal ganglion cells in mice

Abstract: Glaucoma is a group of eye diseases characterized by retinal ganglion cell (RGC) loss and optic nerve damage. Studies, including this study, support that RGCs degenerate and die in a type‐specific manner following the disease insult. Here we specifically examined one RGC type, the intrinsically photosensitive retinal ganglion cell (ipRGC), and its associated functional deficits in a mouse model of experimental glaucoma. We induced chronic ocular hypertension (OHT) by laser photocoagulation and then characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 58 publications
2
10
0
Order By: Relevance
“…Immediately following vis-OCT imaging, mice were sacrificed, perfused, and the retinas were dissected and immunostained with rbpms, an RGC marker [43]. Flat-mounted retinas were then imaged by confocal microscopy [35, 43]. As demonstrated in the schematic representation of the flattened retina in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Immediately following vis-OCT imaging, mice were sacrificed, perfused, and the retinas were dissected and immunostained with rbpms, an RGC marker [43]. Flat-mounted retinas were then imaged by confocal microscopy [35, 43]. As demonstrated in the schematic representation of the flattened retina in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, one type of RGCs, the ipRGC, is involved in circadian functions [58], and at least one subtype, the M4 ipRGCs, has higher distribution in the superior and temporal retina [54]. It has been found that ipRGC’s are more resistant to chronic elevation of IOP [43] and ONC injury [59] than general RGCs. The retained circadian functions of the mice after chronic IOP elevation also suggest a normal function of ipRGCs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations